AN EFFICIENT AND FACILE SYNTHESIS OF SOME ETHYL -1-CARBAMOYL-4- (2 OR 4-SUBSTITUTED PHENYL)-6-METHYL-2-OXO-1, 2, 3, 4- TETRAHYDROPYRIMIDINE-5-CARBOXYLATE THROUGH ULTRASOUND ACCELERATED VILSMEIER-HAACK REACTION AND THEIR SCREENING AS ANTIPLATELET & ANTICAR - N.R.CHATTERJEE,; D.C.SHARMA,; G.R.JADHAV,; B.G.CHANDAK, (International Journal of Pharma and Bio Sciences, 2010)
An efficient synthesis of some 5-ethoxycarbonyl-4-(2 or 4-substituted phenyl)-6-methyl-2-oxo1,2,3,4-tetrahydropyrimidine-2(1H)-carboxylic acids (3) has been reported through ultrasonically assisted Vilsmeier-Haack reaction of their corresponding 5-ethoxycarbonyl-4-(4-substituted phenyl)6-methyl-3,4-dihydropyrimidin-2(1H)-ones (1) using silica gel as catalyst yielding N-1-formyl derivative (2); followed by oxidation with 30% H2O2. The N-1 carboxylic acids (3) thus obtained were converted to their amide derivatives (4) in very good yield by classical reactions. Preliminary pharmacological screening of these novel carboxamides indicated that they possessed significant antiplatelet activity and moderate anticardiac activity.